PERLUASAN PUSAT KEGIATAN WARGA RT.002 RW.003 ASEMPAYUNG, KELURAHAN GEBANG PUTIH, KECAMATAN SUKOLILO, KOTA SURABAYA - Prabani Setio Hastorahmanto; Lucia Ina Trisyanti; Anas Hidayat; Widriyakara Setiadi; Heristama Anugerah Putra; Josephine Roosandriantini; Yohanes Kristianus Harianto; Valerio Sultan Agni; James Efandaru (Universitas Sanata Dharma, 2022)
Residents of RT.02 RT.003 Asempayung, in general, are indigenous people who have lived in the area for generations. The rapid development of the population has resulted in the narrowing of residential land because it has been divided among the heirs of children and grandchildren. The limited open land has resulted in several community activities being carried out on environmental roads. The Abdimas empowered the community to participate in mutual cooperation in completing the program. UKDC Architecture Study Program will carry out an activity program for the expansion of the community activity center in 2022 by: 1) Empowering the community to participate in the expansion of the activity center; 2) Together with the residents, they will procure sewer cover material as an expansion of the community's activity center. This is largely determined through good communication, social approaches and intense interaction with residents. The output obtained from this community service program is the expansion of the activity center for the residents of Asempayung RT.02 RW.003. This activity will cover the sewerage of dirty water which is about 2.5 meters wide. Closing the channel will form a space above it, which can be used as a center for residents' activities.